2021
DOI: 10.1002/smtd.202100012
|View full text |Cite
|
Sign up to set email alerts
|

Activation Strategies of Perovskite‐Type Structure for Applications in Oxygen‐Related Electrocatalysts

Abstract: The oxygen‐related electrochemical process, including the oxygen evolution reaction and oxygen reduction reaction, is usually a kinetically sluggish reaction and thus dominates the whole efficiency of energy storage and conversion devices. Owing to the dominant role of the oxygen‐related electrochemical process in the development of electrochemical energy, an abundance of oxygen‐related electrocatalysts is discovered. Among them, perovskite‐type materials with flexible crystal and electronic structures have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 217 publications
0
20
0
Order By: Relevance
“…Perovskite oxides (ABO 3 ) have recently been under the spotlight due to their ordered atomic arrangement and highly flexible electronic structure. It is found that the original oxidation state of the catalytic material plays a crucial role in the formation of an active site after the reconstruction. Therefore, optimizing the electronic structure of perovskite by A-site or B-site substitution has been well demonstrated, such as B-site Fe-substitution optimized Co-based perovskite oxide catalysts to form a highly active surface amorphous oxyhydroxide layer. ,, Moreover, precise A-site Ce doping LaNiO 3 exhibits a dynamic reconstruction feature with the growth of a self-assembled NiOOH active layer during OER . Therefore, the surface reconstruction of perovskite is beneficial to obtain high activity.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite oxides (ABO 3 ) have recently been under the spotlight due to their ordered atomic arrangement and highly flexible electronic structure. It is found that the original oxidation state of the catalytic material plays a crucial role in the formation of an active site after the reconstruction. Therefore, optimizing the electronic structure of perovskite by A-site or B-site substitution has been well demonstrated, such as B-site Fe-substitution optimized Co-based perovskite oxide catalysts to form a highly active surface amorphous oxyhydroxide layer. ,, Moreover, precise A-site Ce doping LaNiO 3 exhibits a dynamic reconstruction feature with the growth of a self-assembled NiOOH active layer during OER . Therefore, the surface reconstruction of perovskite is beneficial to obtain high activity.…”
Section: Introductionmentioning
confidence: 99%
“…The desirable OER electrocatalyst is expected to possess moderate surface oxygen interaction energy in accordance with Sabatier's principle. The regulation of B‐site cations with complex spin configurations and polyvalent states in the perovskite is of great significance to tune its electronic structure and electrical transport properties for optimized OER performance 61 …”
Section: Resultsmentioning
confidence: 99%
“…Some of these published articles deal with perovskite oxides for photocatalysis purposes [560][561][562][563][564][565][566][567][568][569][570][571] but some of them provide an overview of the knowledge of water electrolysis on perovskite-based materials. 24,86,451,[572][573][574][575][576][577][578][579][580][581][582][583][584][585][586][587][588][589] Numerous advanced theoretical and experimental studies have been published, leading to a variety of perovskite-type oxides as potential ORR, 590 OER [591][592][593][594][595][596][597]611 and HER [598][599][600]619 electrocatalysts. Because of the severe oxidative conditions experienced at OER anodes, and the highly-reductive conditions at the HER cathode, metal oxides have traditionally been found...…”
Section: Perovskite-based Electrode Materials For Oxygen and Hydrogen...mentioning
confidence: 99%